The Impact of Changes to the Regional Head Election Law in Indonesia - Laode Rachmad Zulpril Andito (Universitas Muhammadiyah Sumatera Utara, 2026)
The amendment to the Regional Head Election Law represents a further step towards reforming the national political system, improving the quality of local democracy, and demanding efficiency in the implementation of regional head elections. This article analyzes the impact of regulatory changes on the implementation of regional head elections in Indonesia. The research method uses normative juridical methods with a comparison of laws and regulations, analysis of official documents, and a review of scientific literature. The results show that year after year, the changes in the law strengthen the institutional system, clarify the mechanism for nominating regional heads, and improve the quality of regional head election standards. It cannot be denied that negative impacts on the implementation of regional head elections from year to year include increased political costs, horizontal conflicts, and challenges in maintaining the neutrality of the state bureaucracy. This article explains the importance of continuous reform in regional head election regulations so that they run according to the principles of transparent, accountable, and integrated democracy.